Motor Speed Control Using IC Timer 555 Based on Proteus Software Simulation - Suherman; Ulfa Dina Zakia (Fakultas Teknik Universitas PGRI Banyuwangi, 2024)
This simulation aims to determine the effect of the percentage of potential resistance on the waves produced from a dc motor circuit using IC 555 as a wave generator. The simulation results show that the smaller the percentage of potential resistance, the faster the RPM on the motor with the greater the voltage and amperage on the motor. The resulting wave has a very strong influence on the potential resistance, the smaller the resistance, the longer the wave produced by the IC 555 will be and will have a relatively short density. Analysis shows that changes in resistance percentage affect the voltage, amperes, RPM and waves on the motor